Similarities and differences in the functions of non-suicidal self-injury (NSSI) across gender non-conforming and cisgender young adults - Lutz, Nina M. (J Affect Disord, 2024)
BACKGROUND: Non-suicidal self-injury (NSSI) can be motivated by a broad range of functions and many individuals report multiple reasons for self-injuring. Most NSSI research has involved predominantly female samples and few studies have examined gender similarities and differences in function endorsement. METHODS: We characterise the prevalence and versatility of NSSI functions within a gender-diverse online sample of cisgender women (cis-women; n = 280), cisgender men (cis-men; n = 176), and transgender, non-binary, and other gender non-conforming young adults (TGNC; n = 80) age 18–30 (M = 23.73, SD = 3.55). The Ottawa Self-Injury Inventory (OSI-F) assessed 24 intrapersonal and social functions across nine domains: affect regulation, self-punishment, anti-dissociation, anti-suicide, sensation seeking, sexuality, interpersonal influence, and body image. RESULTS: TGNC participants and cis-women were significantly more likely to report intrapersonally motivated NSSI and greater function versatility than cis-men. Low mood, emotional distress, suicidality, and trauma symptomology appeared to contribute to gender differences in function endorsement. Gender similarities also emerged; across groups, intrapersonal functions were substantially more common than social functions, and the most endorsed domains were affect regulation and self-punishment. No domains were gender specific. LIMITATIONS: The OSI-F was developed from majority female samples and may not adequately capture the experiences of other gender groups. CONCLUSIONS: Interventions which reduce distress and strengthen emotion regulation are likely to benefit individuals who self-injure regardless of gender. However, most individuals report multiple NSSI functions and person-centred interventions which address this complexity are needed. Future research should develop gender-informed treatment models which consider the unique experiences of TGNC individuals and cis-men who self-injure.